ANALISIS STRUKTUR TARIF PAJAK DALAM MELIHAT KEPATUHAN WAJIB PAJAK BADAN (Studi Kasus pada PT. Bank Pembangunan Daerah Sulawesi Tenggara) - Akib, Mulyati (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2019)
This study aims to determine and analyze the structure of tax rates to see taxpayer compliance which is PT. Bank Pembangunan Daerah of Southeast Sulawesi. Data collection methods used in this study are interviews, documentation and library studies. This study is descriptive analysis research. The results of this study indicate that companies that become taxpayers must have proof of registration as a taxpayer in the form of a Taxpayer Identification Number. PT. Bank Pembangunan Daerah of Southeast Sulawesi has registered as a taxpayer and had a Taxpayer Identification Number. The imposition of corporate tax rates is based on the gross circulation of the entity. PT. Bank Pembangunan Daerah of Southeast Sulawesi is subject to 25% PPh tariff since its gross circulation value exceeds Rp. 4,800,000,000. PT. Bank Pembangunan Daerah Southeast Sulawesi also reports and pays the tax liability on time and precisely the amount in accordance with the tax rates and the time stated in the SPT.